Lowering Nitrogen and Increasing Potassium Application Level Can Improve the Yield and Quality of Panax notoginseng - Ou, Xiaohong; Cui, Xiuming; Zhu, Duanwei; Guo, Lanping; Liu, Dahui; Yang, Ye (Frontiers in Plant Science, 2020)
Excessive nitrogen (N) application and potassium (K) supplement deficient is a common problem in Panax notoginseng cultivation. However, synergistic effects of lowering N and increasing K application on yield and quality of P. notoginseng have not been reported. This study first evaluated the N and K levels in P. notoginseng planting soil. Field experiments in two locations with different N and K combined application were conducted to study the effects on yield and quality. Then, the saponins accumulation mechanism were explored by pot and hydroponic culture with 2 or 3 years old seedlings. The results showed that 70% of P. notoginseng cultivation fields reached abundant levels of total nitrogen (TN) but had deficient levels of total potassium (TK), so that the TN/TK value was adverse to accumulate biomass and saponins (PNS) for P. notoginseng. Compared to the conventional N and K application (N:K = 2:1), lowering N and increasing K application (N:K = 1:2) decreased root rot rate by 36.4%-46.1%, increased survival rate, root biomass and yield, as well as PNS content by 17.9%-18.3%, 5.7%-32.9%, 27.8%-57.1%, 5%-10%, respectively. The mechanism of lowering N and increasing K application on the PNS content improving were due to the decreasing of N/K value, which promoted photosynthesis, sugar accumulation, and the expression of saponin biosynthesis genes. Therefore, lowering N and increasing K application to the ratio of 1:2 would have great potential to improve the synergistic effect on yield and quality of in P. notoginseng cultivation.